Effect of planting time on the productivity and the oldage of some potato varieties, and quality of the production. - Omar, Mohammad; Obaed, Hassan; Abu Trabi, Bassam (Latakia University Journal -Biological Sciences Series, 2013)
The aim of this study was comparing between three potato cultivars: "Afamia, Loulou and Tadmur" which are planted in two different times (spring time and autumn time), for the plant old age and some yield properties and some quality properties. After ripping and harvesting, result showed superior Loulou to Afamia and Tadmur in most parameters at the two planting times, so the productivity of Loulou was more than Afamia by 6 ton/h in the spring and 1.6 ton/h in the autumn. For the starch and dry matter content, Loulou tubers in the two planting times contained more amount than the other cultivars, and more than the global average (%14 starch, %22 dry matter). Afamia plants life was the shortest, so they took 102 days in spring and 104 days in autumn to reach to the maturation stage. On the other hand, the spring planting time was superior to the autumn planting time in various studied parameters, in spite of the plants grown in spring were the shortest in its life than autumn plants.